The Influence Of Social Media, Price And Product Quality On Purchasing Decisions On Albaik Chicken In Bengkulu City - Ariyansyah, Ardika Okta; Susena , Karona Cahya; Febliansyah, M Rahman (Utami Publisher, 2025)
This type of research is explanatory research, namely a study to determine whether there is a relationship between the variables studied. Based on the background that has been discussed, several problems arise, namely whether social media affects purchasing decisions at Allbaik Chicken in Bengkulu City Does price affect purchasing decisions at Allbaik Chicken in Bengkulu City Does product quality affect purchasing decisions at Allbaik Chicken in Bengkulu City Does Social Media, Price, and Product Quality affect purchasing decisions at Allbaik Chicken in Bengkulu City Based on the formulation of these problems, the objectives in this study are to determine the effect of social media on purchasing decisions at Allbaik Chicken in Bengkulu City to determine the effect of price on purchasing decisions at Allbaik Chicken in Bengkulu City to determine the effect of product quality on purchasing decisions at Allbaik Chicken in Bengkulu City to determine the effect of Social Media, Price, and Product Quality on purchasing decisions at Allbaik Chicken in Bengkulu City the results of the study state that there is an influence of social media (X1) on purchasing decisions (Y) Allbaik Chicken with a tsig. value < α (0.005 < 0.05) and a tcount> ttable value (2.924> 1.67065) thus Ho is rejected and Ha is accepted. From the significance value obtained that variable X1 has an effect on purchasing decisions (Y). There is an effect of price (X2) on purchasing decisions (Y) Allbaik Chicken with a tsig. value < α (0.010 < 0.05) and a tcount> ttable value (2.672> 1.67065) thus Ho is rejected and Ha is accepted. From the significance value obtained that the X2 variable has an effect on purchasing decisions (Y). There is an effect of product quality (X3) on purchasing decisions (Y) Allbaik Chicken with a tsig. value < α (0.006 < 0.05) and a tcount> ttable value (2.426> 1.67065) thus Ho is rejected and Ha is accepted. From the significance value obtained that variable X3 has an effect on purchasing decisions (Y). The value of Fsig. < α 0.05 and Fcount > F table (111.421> 2.76) thus it can be concluded that together the independent variables affect the dependent variable.